PERANCANGAN APLIKASI ADMINISTRASI PERSURATAN BERBASIS MOBILE MENGGUNAKAN FLUTTER UNTUK MENINGKATKAN EFEKTIVITAS PENGARSIPAN DI SMK IT AL-JUNAEDIYAH - Fitria Asti Putri (Jurnal Teknologi Informatika dan Rekayasa Terapan, 2026)
The development of information technology drives digital transformation in educational administration. At SMK IT Al-Junaediyah, letter management is still manual, leading to recording errors, difficulty in searching for archives, and delays in reporting. This study aims to design and implement a mobile-based letter administration application to improve archiving effectiveness. The method used is the Software Development Life Cycle (SDLC) Waterfall model which includes needs analysis, design, implementation, testing, and maintenance. The application was developed using Flutter (Dart) and SQLite for offline storage. Black Box testing results show that all main features function with a 100% success rate in the test scenario, archive search time is reduced from an average of 2–5 minutes to <5 seconds, and report generation is automated. In conclusion, the mobile application can improve the efficiency, accuracy, and speed of letter management.